(untitled) (Research, Society and Development, 2020)
The health education process focuses on knowing how to teach people how to pass on certain information to someone who does not know or who needs to update themselves on a specific topic related to aspects related to health. The general objective of the research is to analyze what research, in the last four years, has proposed about continuing education in health for nurses. This is an integrative review study, through electronic search of articles indexed in SCIELO, based on the following keyword: continuing health education for nursing professionals, with 10 articles on the proposed themes being analyzed. As a result, continuing education in health in the field of nursing shows the understanding that the subject must have the current knowledge to achieve a certain objective in pursuing his professional career, such a career that include effective means of improvement for professional achievement and offer comprehensive quality of care for the whole society, always evaluating the importance and need of the patient as a whole and also being viable for the implementation of nursing care, enabling human dialogues which match the health issues to the individuals, with the care provided through qualification. Thus, with the results of this research, it is expected to make a clear contribution, with professional nurses in general, that the quality of care is closely linked to their constant need for participation in health education programs.